2000
DOI: 10.1002/1099-078x(200007/09)15:3<243::aid-bin59>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Using self-monitoring procedures to increase on-task behavior with three adolescent boys with brain injury

Abstract: The eects of self-monitoring on-task behavior, accuracy, and productivity were assessed with three adolescent boys with brain injury. A combined multiple baseline across subjects and alternating design schedule was used. Participants were taught to self-record the three dependent variables while they were completing independent math assignments. A tape-recorded audio tone was used as a cue to self-record. Research assistants recorded occurrence of on-task behavior using 10 s interval recording. They also repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 11 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Another tactic for improving everyday functioning is to increase error detection or monitoring. That is, because it is virtually impossible to eliminate all errors in everyday tasks, some investigators have focused on promoting task monitoring and error detection (Levine et al, 2000; Manly, Lewis, Robertson, Watson, & Datta, 2002; Norman, 1990; Selnick & Savage, 2000; Winocur et al, 2000). Indeed, prior studies have demonstrated that dementia patients corrected 79% of detected errors on the NAT (Giovannetti, Libon, & Hart, 2002); this suggests that improving error detection might facilitate error correction and task accomplishment.…”
mentioning
confidence: 99%
“…Another tactic for improving everyday functioning is to increase error detection or monitoring. That is, because it is virtually impossible to eliminate all errors in everyday tasks, some investigators have focused on promoting task monitoring and error detection (Levine et al, 2000; Manly, Lewis, Robertson, Watson, & Datta, 2002; Norman, 1990; Selnick & Savage, 2000; Winocur et al, 2000). Indeed, prior studies have demonstrated that dementia patients corrected 79% of detected errors on the NAT (Giovannetti, Libon, & Hart, 2002); this suggests that improving error detection might facilitate error correction and task accomplishment.…”
mentioning
confidence: 99%
“…Like Ylivasker (1995, 2003), Koegel and Koegel (1986), and Selznick and Savage (2000) improved academic performance with antecedent management. Koegel and Koegel (1986) found that interspersed maintenance tasks improved the academic performance and social affect of an eight-year-old stroke victim.…”
Section: Introductionmentioning
confidence: 91%
“…On the other hand, several studies employed multiple baseline designs, alternating treatment designs, and reversal designs that demonstrated a clear treatment effect (i.e. Hegel, 1988;Kennedy, 1994;Selznick & Savage, 2000, Slifer et al, 1993.…”
Section: Experimental Limitationsmentioning
confidence: 99%
See 1 more Smart Citation